El Niño Enhances Exposure to Humid Heat Extremes With Regionally Varying Impacts During Eastern Versus Central Pacific Events - Zachary M. Menzo; Christina Karamperidou; Qinqin Kong; Matthew Huber (Geophysical Research Letters)
Abstract Humid heat extremes, characterized by high wet bulb temperature (Tw), pose significant health risks. While strong El Niño events are known to affect the frequency of extreme Tw days, the distinct impacts of Central Pacific (CP) and Eastern Pacific (EP) El Niño events remain understudied. Using a 12‐member CMIP6 ensemble at discrete global warming targets (+1.5, 2, 3, 4°C), this study shows progressively enhanced humid heat extent during EP events primarily in Mainland Southeast Asia, while South Asia experiences regionally opposing effects from EP and CP events. EP and CP events drive distinctly different, regionally varying patterns of dangerous Tw, yet both significantly increase the affected population and area impacted by humid heat extremes at all global warming levels. This amplification surpasses the impact of an additional degree of global warming, highlighting El Niño's compounding effect on heat stress threats across warmer climates.